Association between Helicobacter pylori Infection and Chronic Urticaria: A Meta-Analysis - Huiyuan Gu; Lin Li; Min Gu; Guoxin Zhang (Gastroenterology Research and Practice)
Background. Some studies have shown the possible involvement of Helicobacter pylori (H. pylori) infection in chronic urticaria, but the relationship remains controversial. The aim of this meta-analysis was to quantitatively assess the association between H. pylori infection and chronic urticaria. Methods. Observational studies comparing the prevalence of H. pylori infection in patients with chronic urticaria and control subjects were identified through a systematic search in MEDLINE and EMBASE up to July 2014. H. pylori infection was confirmed by serological or nonserological tests. For subgroup analyses, studies were separated by region, publication year, and H. pylori detection method to screen the potential factors resulting in heterogeneity. Results. 16 studies involving 965 CU cases and 1235 controls were included. Overall, the prevalence of H. pylori infection was higher in urticarial patients than in controls (OR = 1.66; 95% CI: 1.12–2.45; P=0.01). This result persisted in subanalysis of nine high-quality studies (OR = 1.36; 95% CI: 1.03–1.80; P=0.03). Subgroup analysis showed that detection method of H. pylori is also a potential influential factor for the overall results. Conclusions. Our present meta-analysis suggests that H. pylori infection is significantly, though weakly, associated with an increased risk of chronic urticaria.